Kualitas Produk Dan Pelayanan Restoran Cepat Saji Dalam Menghadapi Pesaing di Kabupaten Sumenep (Studi Pada Toby’s Fried Chicken) - Very Andrianingsih (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2020)
Product quality and service affect the progress of a restaurant. The rise of business competition requires businesses to continue to innovate so as not to compete. Restaurant business owners must always maintain and improve the quality of their products and services. The quality of products and services is a means to compete with competitors. Quality products and services will help restaurant business owners to get a strategic market position. This study aims to find out how the quality of Toby’s Fried Chicken products and services in Sumenep Regency. The sampling technique in this study used Purposive Sampling by determining key informants as many as 1 person, 2 main informants, supporting informants as many as 5 people and using data collection techniques, including observation, interviews, and documentation. The results of this study indicate that Toby’s Fried Chicken products in the latest Fried Chicken products are still undercooked, Toby’s Fried Chicken has not released a variety of new products with a steady innovation. The service of Toby’s Fried Chicken is quite good with the good attitude shown by the waiter, but for the arrangement of the place there is no attractive design to be enjoyed by customers. Toby’s Fried Chicken continues to maintain and improve its quality, both in terms of products and services to be able to compete with fast-food restaurants like Toby's.